Comparison of California Bearing Ratio (CBR) Value Based on Cone Penetration Test (CPT) and Dynamic Cone Penetrometer (DCP) - Reki Arbianto; Teguh Yuono; G Gunarso (JACEE (Journal of Advanced Civil and Environmental Engineering), 2021)
In civil engineering, land is important because as a place for building infrastructure to be built, so that the building infrastructure on it is stable, adequate carrying capacity is needed. The amount of soil bearing capacity can be determined in several ways, including the California Bearing Ratio (CBR) Field Test, Cone Penetration Test (CPT) and Dynamic Cone Penetrometer (DCP). The CBR and DCP tests are often used to determine the level of surface soil density on road structures, while CPT is usually used to determine the hard soil layer on the building structure. However, in certain situations Sondir and DCP data are often used to predict the CBR value, because the test is quite practical and efficient compared to the CBR test. CBR testing requires heavy equipment which in most small-scale projects is not available. In this study, we compared the CBR value based on the data obtained from the Sondir and DCP tests. Data collection was carried out in Surakarta and its surroundings. Based on the test results, the CBR value generated from the DCP test tends to be smaller than that from the CPT test with a ratio of 0.62: 1. This study resulted in the relationship between CBR values from the results of the CPT and DCP tests shown in the following equation: CBR (DCP) % = 0.2552 CBR(CPT) + 2.6306 and CBR (DCP) % = 0.617 CBR(CPT).